Customer Purchase Intentions on Hijab Fashion: The Role of Social Media Marketing Instagram and Product Quality - Nugroho Hardiyanto; Hewage Lakshi Krishani Perera; Lusianus Kusdibyo (Politeknik Negeri Bandung, 2020)
The objective of this research is to measure the influence of product quality and social media Instagram on customer purchase intention of hijab fashion. The Theory of Reasoned Action (TRA) was used to explain the relationship of the variables affecting customer purchase intentions. A quantitative method was used in this study and the structural equation modeling (SEM) was employed to test the research hypotheses. The data collection was carried out using a purposive sampling method. A total of 210 respondents were gathered during the data collection period. The results showed that social media marketing Instagram and product quality influence customer purchase intention. This finding implies to fashion store managers to consider not only product quality in selling the hijab but also the social media marketing Instagram in encouraging customer purchase intentions.